(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The concept has been studied fuzzy- Socle- acobson–Two-Absorbiang submodules and some fuzzy relationships According to the concept above. Where the new definition was named fuzzy Socle- acobson–Two-Absorbiang, we used a few algebraic techniques to determine the rapport between fuzzy Two-Absorbing and fuzzy Socle- acobson–Two-Absorbiang. In addition to studying functions and some other related concepts. Our study’s ramifications can be utilized to identify novel ideas that rely on hazy Socle- acobson–Two-Absorbiang concepts. In addition, we used some of the basics of modules and partial modules to prove that the intersection process in the new concept does not necessarily have to be achieved. In this study, the functions in modules and their relationship with the same concept and investigated some of the properties of those functions. The properties of the distributive module were also used in this research to achieve some theorems. In this research, it was also proven that the process of combining does not necessarily occur between two sub modules that bear the characteristics of the studied concept. Results: Using previous properties to find a new fuzzy sub module and a new definition. Conclusions: In this work, we presented a new type of fuzzy sub modules using the properties of addition and intersection between them and some properties of the new fuzzy submodule.